2018
DOI: 10.3390/ijms19072030
|View full text |Cite
|
Sign up to set email alerts
|

A Current Overview of the Biological and Cellular Effects of Nanosilver

Abstract: Nanosilver plays an important role in nanoscience and nanotechnology, and is becoming increasingly used for applications in nanomedicine. Nanosilver ranges from 1 to 100 nanometers in diameter. Smaller particles more readily enter cells and interact with the cellular components. The exposure dose, particle size, coating, and aggregation state of the nanosilver, as well as the cell type or organism on which it is tested, are all large determining factors on the effect and potential toxicity of nanosilver. A hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(117 citation statements)
references
References 197 publications
(501 reference statements)
6
111
0
Order By: Relevance
“…Numerous studies have demonstrated the potency of AgNPs to induce deleterious biological and cellular effects. 1 The toxicity of AgNPs was shown to be a result of an interplay of the particle uptake, dissolution and induction of oxidative stress. 2 Indeed, excessive production of reactive oxygen species (ROS) in cells by direct interaction with particles and/ or dissolved species is currently accepted as one of the main mechanisms of cellular toxicity of engineered nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated the potency of AgNPs to induce deleterious biological and cellular effects. 1 The toxicity of AgNPs was shown to be a result of an interplay of the particle uptake, dissolution and induction of oxidative stress. 2 Indeed, excessive production of reactive oxygen species (ROS) in cells by direct interaction with particles and/ or dissolved species is currently accepted as one of the main mechanisms of cellular toxicity of engineered nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…2 Indeed, excessive production of reactive oxygen species (ROS) in cells by direct interaction with particles and/ or dissolved species is currently accepted as one of the main mechanisms of cellular toxicity of engineered nanoparticles. 1,[3][4][5] ROS have many signaling and information functions; however, excessive ROS can collapse the antioxidant defense system, leading to the damage of DNAs, lipids and proteins. 5,6 Antioxidant enzymes have been recognized as important modulators in AgNP induced oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the attributed properties of AgNPs, mainly as antimicrobial agent (Maillard and Hartemann 2012), this engineered nanomaterial is placed among the most often incorporated in nanofunctionalized consumer products (Zhang et al 2016). With regard to their potential harmful effects, different studies have been conducted to understand the underlying mechanisms of action (Stensberg et al 2011;Schluesener and Schluesener 2013;McGillicuddy et al 2016;Cameron et al 2018). The obtained results suggest that AgNPs penetrate cell membranes in a size-dependent ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer properties of silver nanoparticles have been identified in many studies. Also, silver nanoparticles contribute to DNA damage, increase the expression of the caspase 3 protein and trigger apoptosis, and thus lead to the inhibition of proliferation, through transducing cell death signals, which is very important in cancer treatment (14). Silver nanoparticles can interact with membrane proteins and activate cellular signaling pathways that lead to cell division inhibition (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%